Political economy of U.S. sanctions toward Myanmar - WAI SETT, Han (KDI School, 2016)
Do international sanctions make difference? This has been one of the central questions long debated in foreign policy circles and international relations academia. In this regard, the U.S. sanctions toward Myanmar is an important case involving the policy goal of regime change and democratization. This study focuses on three central questions: What is the economic impact of U.S. sanctions on Myanmar’s export? How did the military regime respond politically to the sanctions? What is the overall degree of effectiveness of U.S. sanctions in achieving the policy goal? As from the first attempt, it is found that the main hypothesis of U.S. sanctions being ineffective in impairing Myanmar’s export cannot be rejected due to significant results of increased export to non-US countries during the sanction period despite the zero export to the U.S. according to the gravity model analysis. However, the growth rate of Myanmar’s export can be concluded as a slower rate when it is compared with the neighboring countries especially when newly industrializing countries such as Thailand and Malaysia are included in the analysis. The second attempt of analysis on the export structure proved that Myanmar become more dependent on natural resource exports especially natural gas and gemstones mainly to Thailand and China. From this analysis, it can be summarized that the military regime’s responses to the U.S. policy actions manifested the high degree of political impact of sanctions.
Thesis(Master) --KDI School:Master of Public Policy,2016